Risk Factors for Cardiovascular Diseases: a Study at National Institute of Cardiovascular Diseases (NICVD) (Bangladesh Medical Journal, 2011)
Key words: Risk factors; Coronary Heart Disease (CHD); Systolic Blood Pressure (SBP); Diastolic Blood PRessure (DBP); Body Mass Index (BMI); Waist Hip Ratio (WHR)DOI: 10.3329/bmj.v39i2.7031Bangladesh Medical Journal 2010, 39(2) pp.16-21